Hydrogeology Response to the Coordinated Mining of Coal and Uranium: A Transparent Physical Experiment - Tong Zhang; Xiang He; Kai Zhang; Xiaohan Wang; Yang Liu (Geofluids)
The migration of fracture and leaching solute caused by mining activity is critical to the hydrogeology. To characterize liquid and solid migration in a mining area of intergrown resources, the coordinated mining of coal and uranium was considered, and a physical experiment based on transparent soil was conducted. A well experimental performance of transparent soil composed of paraffin oil, n-tridecane, and silica gel and the leaching solution comprised of saturated oil red O dye was observed for hydrogeology characterization. An “arch-shaped” fracture zone with a maximum height of 90 m above the mined goaf and a “horizontal-shaped” fracture zone with a fractured depth of 9.97–16.09 m in the uranium-bearing layer were observed. The vertical leachate infiltration of 4.83 m was observed in the scenario of uranium mining prior to coal, which is smaller than those in the scenarios of comining of coal and uranium (10.26 m) and coal mining prior to uranium (16.09 m). A slight strata movement below the uranium was observed, and the leaching solution infiltration in the coal mining area was not observed in a short period in the scenario of uranium mining prior to coal; both of those was presented in the scenarios of comining of coal and uranium and coal mining prior to uranium.